O Potęgowej Postaci Mechanicznego Równania Stanu z Uwzględnieniem Temperatury - Klepaczko, J. (Engineering Transactions, 1965)
The conception of mechanical equation of state is analysed, involving strain, strain rate and temperature. Four conditions limiting this conception are introduced. Next, is discussed the exponential law, proposed for constant temperature by B. A. DAVIS, The analysis of existing experimental data shows that each material constant depends on the temperature,therefore the equation in question can be written thus(…), where m(T) denotes the strain-hardening exponent n(T)-the rate sensitivity and B(T)-the plastic modulus, all the three quentities being dependent on the temperature. The fundamental equations are obtained from an analysis of experimental results of tension or compression tests at constant strain rates and various temperatures. If the temperature is treated as a parameter, these equations describe in a satisfactory manner the first stage of creep and the phenomenon of relaxation. If the temperature depends on time, differential equations are obtained describing both phenomena. If the variability of temperature is prescribed, results can be obtained numerically. The obtained equations determine the influence of strain, strain rate and temperature on the strain-hardening curve and describe the behaviour of metals such as aluminium, copper, lead etc.